Feasibility of Fish Oil Supplementation on Headache Symptoms and Blood Lipids in Migraine Patients - En‐Ling Yeh; Chun‐Pai Yang; Shu‐Wen Lin; Hsueh‐Fang Wang (Brain and Behavior)
ABSTRACT Objectives Migraine is a chronic, recurring, and disabling disease. Fish oil intervention was used to investigate its effects on headache symptoms and blood lipids of migraine patients. Design All subjects were collected at the Kuang Tian General Hospital from March 2020 to May 2021. Experimental group subjects took 1 g/time of fish oil (including EPA 900 mg/tablet) after breakfast and dinner. Placebo group subjects took 100% soybean oil twice daily. Before and after the test, the migraine improvement questionnaire was used to analyze headaches during attacks, dietary intake, and headache triggers. Results The average age of the 47 subjects in this study was 40.3 ± 9.2 years old, the body mass index (BMI) was 24.3 ± 6.0 kg/m2. At Week 12, subjects in the fish oil group were significantly improved relative to the control group (p < 0.05). Blood lipid indexes TC, LDL‐C, and TG were reduced, and the frequency, duration, and pain degree of migraine. Conclusion Fish oil may be used as an adjunctive therapeutic food for relieving migraine attack symptoms and blood lipids.